MOGOK KERJA PERSPEKTIF KEADILAN HUBUNGAN INDUSTRIAL PANCASILA DI MASA PANDEMI COVID-19 - Sarudi Sarudi (Media Keadilan: Jurnal Ilmu Hukum, 2022)
This research aims to analyze the problem of strikes on the perspective of industrial relations justice, especially during the Covid-19 pandemic. Given that many workers' rights cannot be paid by the employer, in the form of wages, and severance at some of the consequences arising from the laying off of workers. Using Normative research with data is obtained through library research in the form of primary, secondary and tertiary legal materials. Analyzed through qualitative descriptive methods. The results of the study are in the form of, First, weak law enforcement related to strikes caused by several factors such as force majour conditions in the form of the Covid-19 pandemic. Second, the condition of the company that does not allow to fulfill the rights of workers related to wages and severance at the time of being laid off, so that the suspension of payments is carried out. This has not fulfilled the aspect of industrial relations justice that must actually be fulfilled by the employer for any reason. Due to the absence of a meeting point of negotiation between workers / unions and companies, the constitutional effort that can be taken is a strike. Keyword: Strike; Pancasila Industrial Relations Justice; Covid-19. ABSTRAKPenelitian ini bertujuan untuk menganalisis permasalahan mogok kerja pada perspektif keadilan hubungan industrial, khususnya di masa pandemi Covid-19. Mengingat bahwa banyaknya hak-hak pekerja yang tidak bisa ditunaikan oleh pemberi kerja, berupa Upah, dan pesangon pada beberapa akibat yang ditimbulkan dari dirumahkannya pekerja. Menggunakan penelitian Normatif dengan data diperoleh melalui library research berupa bahan hukum primer, sekunder dan tersier. Dianalisis melalui metode deskriptif kualitatif. Hasil penelitian berupa, Pertama, lemahnya penegakan hukum terkait mogok kerja yang disebabkan beberapa faktor seperti, adanya kondisi force majour berupa pandemi covid-19. Kedua, kondisi perusahaan yang tidak memungkinkan untuk memenuhi hak-hak pekerja terkait upah dan pesangon pada saat akan dirumahkan, sehingga dilakukan penangguhan pembayaran. Hal tersebut belum memenuhi aspek keadilan hubungan industrial yang sejatinya wajib dipenuhi oleh pemberi kerja dengan alasan apapun. Akibat tidak adanya titik temu perundingan antara pekerja/serikat pekerja dan perusahaan, maka upaya konstitusional yang dapat ditempuh adalah mogok kerja.